2021
DOI: 10.29309/tpmj/2021.28.02.4699
|View full text |Cite
|
Sign up to set email alerts
|

Burden and baseline characteristics of patients with decompensated liver disease in Tertiary Care Hospital Gujrat.

Abstract: Objective: To determine the load, clinical and laboratory findings of the patients with decompensated cirrhosis admitted in medical department of tertiary care hospital and to make plan for the improvement of these patients. Study Design: Cross Sectional study. Setting: Department of medicine of Aziz Bhatti Shaheed Teaching Hospital, Gujrat. Period: from 1st January 2019 to 31st March 2019. Material & Methods: All 964 patients who were admitted included in study, clinical and laboratory features of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the process of clinical treatment, patients do not have enough grasp of the disease, have poor management methods, and have behaviors such as self-return and drug discontinuation, resulting in ineffective disease control [ 2 ]. Relevant studies have found that better health services are conducive to improving patients' long-term self-control ability, improving clinical manifestations, alleviating disease, and improving the quality of daily life.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of clinical treatment, patients do not have enough grasp of the disease, have poor management methods, and have behaviors such as self-return and drug discontinuation, resulting in ineffective disease control [ 2 ]. Relevant studies have found that better health services are conducive to improving patients' long-term self-control ability, improving clinical manifestations, alleviating disease, and improving the quality of daily life.…”
Section: Introductionmentioning
confidence: 99%